The impact of a peer-to-peer mentoring program on university choices and performance - Stefania Bortolotti; Annalisa Loviglio (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2024)
We study the impact of a personalized mentoring program on university enrollment choices and academic outcomes. Conducting a randomized controlled trial among 337 high school students, we find that the program significantly influences students' decisions, increasing the likelihood of choosing a field aligned with their mentor's by 22 percentage points, representing a 45% increase from the baseline. Notably, the program also shifts preferences towards STEM/Economics fields, enhancing prospective wages by 3.1-3.7%, without negatively impacting university performance. These findings underscore the mentorship's potential to guide students towards more informed and beneficial educational choices.
Keywords: A20; C93; I23; I26; 330; mentoring; university choices; RCT